Skręcanie prętów cienkościennych typu dwuteownika o dwukierunkowej zmienności przekroju - Cywiński, Z. (Engineering Transactions, 1968)
This paper is a continuation of [1] and in a certain meaning also of author's earlier works [4, 5]. The torsion problem of a bisymmetric I-beam is considered, where the web's height and the flanges' width as well change along the length of the beam. The results of the analysis also relate to other practically important open, bisymmetric cross-sections changeable in two directions. The theoretical considerations base on all classic principles of the technical torsion theory of thin-walled bars with constant cross-sections. The author extends W. Z. WLASOW’s sectorial characteristics theory concerning bars with constant cross-sections to bars with bisymmetric cross-sections variable in two directions. The fundamental differential equation of the problem and also the expressions for the internal forces, and normal and shearing stresses, are derived. Table 1 contains a comparison of the obtained results with the adequate taken from [1, 4, 5] in view of the results given by the torsion theory of thin-walled bars with constant cross-sections.